Integrated self‑healing and Qur'anic psychoeducation: effects on meaning in life and end‑of‑life conversation readiness - Elis Hartati; Nur Setiawati Dewi; Megah Andriyani; Selvi Dwi Puji Asih (Universitas Aisyiyah Yogyakarta, 2026)
Older adults are vulnerable to physical, psychological, and spiritual problems that may reduce their sense of meaning in life and readiness to discuss end-of-life (EOL) issues. This study evaluated the effect of integrating self-healing techniques with Qur’an-based psychoeducation on meaning in life and readiness for EOL conversations. A quasi-experimental pretest–posttest control group design was conducted with 120 older adults recruited through purposive sampling from social service homes managed by the Central Java Provincial Government. Participants were assigned to an intervention group (n = 60) or a control group (n = 60). Meaning in life was measured using the Meaning in Life Questionnaire (MLQ), and readiness for EOL conversations was assessed using the Readiness for End-of-Life Conversations (REOLC) scale. Data were analyzed using descriptive statistics, the Wilcoxon signed-rank test, and the Mann–Whitney U test. The intervention significantly improved meaning in life (W = 194.500, p < 0.001; rB = −0.819) and readiness for EOL conversations (W = 103.000, z = −6.266, p < 0.001; rB = −0.901). These findings suggest that integrating self-healing with Qur’anic psychoeducation effectively enhances psychological and spiritual well-being while improving preparedness for EOL discussions. This psychospiritual intervention may serve as a valuable component of gerontological nursing and community-based elderly care programs.